The response of the two interrelated river components, geomorphology and riparian vegetation, to interbasin water transfers in the Orange-Fish-Sundays River Interbasin Transfer Scheme - du Plessis, A J E (Rhodes University, Faculty of Science, Department of Geography, 2000)
The Skoenmakers River (located in the semi-arid Karoo region of the Eastern Cape) is being used as a transfer route for water transferred by the Orange-Fish-Sundays River Interbasin Transfer Scheme. The change in the hydrological regime of this once ephemeral stream to a much bigger perennial river led to dramatic changes to both the physical structure and riparian vegetation structure of the river system. These changes differ for each of the three river sections, the upper,middle and lower reaches. Qualitative, descriptive geomorphological data was gathered by means of field observations and this was then compared to the quantitative data collected by means of surveyed cross-sectional profiles at selected sites along the length of both the regulated Skoenmakers River and a nonregulated tributary of equivalent size, the Volkers River. Riparian vegetation data was gathered by means of plot sampling along belt transects at each site. A qualitative assessment of the vegetation conditions was also made at each site and then added to the quantitative data from the plot sampling. At each site the different morphological units were identified along the cross-section and changes in the vegetation and sediment composition were recorded. Aerial photographs were used as additional sources of data and observations made from these were compared to data gathered in the field. The pre-IBT channel in this river section was formed by low frequency flood flows but the hydrological regime has now been converted to base flows much higher than normal flood flows. Severe incision, erosion and degradation of both the channel bed and banks occurred. In the lower reaches, post-IBT base flows are lower than pre-IBT flood flows and, due to the increased catchment area, the impact of the IBT was better 'absorbed' by the river system. Aggradation and deposition increased for the regulated river in comparison to the non-regulated river due to more sediment introduced The IBT had the greatest impact in the upper reaches of the regulated river due to more sediment introduced at the top of the system.
Keywords: Skoenmakers River (South Africa); Riparian ecology -- South Africa -- Eastern Cape; Geomorphology -- South Africa -- Eastern Cape